prove that

Asked by  | 30th Jun, 2011, 09:34: PM

Expert Answer:

Taking LHS,we have
=cot²A(secA-1)/1+sinA
=cot²A(secA-1)(1-sinA)/((1+sinA)(1-sinA…?
=cot²A(secA-1)(1-sinA)/(cos²A)
=(secA-1)(1-sinA)/(sin²A)
=(secA-1)(secA+1)(1-sinA)/(sin²A)(secA+…?
=(sec²A-1)(1-sinA)/(sin²A)(secA+1)
=(tan²A)(1-sinA)/(sin²A)(secA+1)
=((sin²A)/(cos²A)(1-sinA))/(sin²A)(secA…?
=(1-sinA)/((secA+1)(cos²A))
=sec²A(1-sinA)/(1+secA)=RHS

Answered by  | 30th Jun, 2011, 06:57: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.